Approaching 100Sn : Structural evolution in 98,100Cd via lifetime measurements - Zhang, G.; Zyriliou, A.; Cox, D.; Hrabar, Y. ; 0000-0002-3194-1001; Sarmiento, L. G. ; 0000-0001-7600-2772 (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2025)
The lifetimes of low-lying excited states below the 8+ seniority isomer were directly measured using fast timing detectors in the neutron-deficient isotopes 98,100Cd. This experiment was conducted with the DEcay SPECtroscopy (DESPEC) setup at GSI, where the ions of interest were produced via a fragmentation reaction and identified using the FRagment Separator (FRS) before being implanted in the AIDA active stopper system, and the γ rays emitted during the de-excitation of isomeric states were detected by the LaBr3 FATIMA Array. The newly deduced values for the reduced transition probabilities were compared with shell-model calculations using different interactions and effective charges. The results indicate that, while 98Cd aligns well with a seniority scheme description, in 100Cd the transition strengths among low-lying states are not fully reproduced, and the nature of these states remains an open problem within the present theoretical description. Ultimately, a key element in the description of this region, crucial for nuclear physics and astrophysics, appears to be the proton-neutron term of the nuclear effective interaction.
Publisher Copyright: © 2025 The Author(s)
Keywords: Gamma-ray spectroscopy; Lifetime measurement; Nuclear structure; Radioactive beams